Woven in moonlight - Ibañez, Isabel (Novelist) (Page Street Publishing Co., 2020)
"Ximena is the decoy Condesa, a stand-in for the last remaining Illustrian royal. Her people lost everything when the usurper, Atoc, used an ancient relic to summon ghosts and drive the Illustrians from La Ciudad. Now Ximena's motivated by her insatiable thirst for revenge, and her rare ability to spin thread from moonlight. When Atoc demands the real Condesa's hand in marriage, it's Ximena's duty to go in her stead. She relishes the chance, as Illustrian spies have reported that Atoc's no longer carrying his deadly relic. If Ximena can find it, she can return the true aristócrata to their rightful place."--Jacket flap